Hahira Gold Leaf, February 3, 1972 - Hahira Historical Society (Valdosta State University Archives and Special Collections, 1972)
Digitized surrogate of the Hahira Gold Leaf newspaper for February 3, 1972 from the Hahira Historical Society Collection at Valdosta State University Archives and Special Collections.
1 electronic record (PDF), 6 scanned pages digitized from original print.
Keywords: Hahira (Ga.); Lowndes County (Ga.); Periodicals; Newspapers; Newspapers -- Georgia -- Hahira; Local history